In silico characterization of differentially expressed short-read nucleotide sequences identified in dieback stress-induced transcriptomic analysis reveals their role as antimicrobial peptides - Ijaz, Siddra; Haq, Imran Ul; Malik, Riffat; Nadeem, Ghalia; Ali, Hayssam M.; Kaur, Sukhwinder (Frontiers in Plant Science, 2023)
We investigated the in silico characterization of short-length nucleotide sequences that were differentially expressed in dieback stress-induced transcriptomic analysis. They displayed homology with C terminal flanking peptides and defensins-like proteins, revealing their antimicrobial activity role. Their predicted fingerprints displayed protein signatures related to antimicrobial peptides. These short-length RGAs have been shown to possess structural motifs such as APLT P-type ATPase, casein kinase II (CK2), protein kinase 3, protein kinase C (PKC), and N glycosylation site that are the attributes of disease resistance genes. Prediction of arginine and lysine residues in active binding sites in ligand docking analysis prophesied them as antimicrobial peptides due to their strong relation with antimicrobial activity. The in-silico structural-functional characterization has predicted their role in resistance against microbial pathogens. The predicted antimicrobial peptide regions showed their homology with the signature domain of PR-5-like protein and AMP family Thaumatin.